A robust pipeline with high replication rate for detection of somatic variants in the adaptive immune system as a source of common genetic variation in autoimmune disease. (12th December 2018) - Van Horebeek, Lies; Hilven, Kelly; Mallants, Klara; Van Nieuwenhuijze, Annemarie; Kelkka, Tiina; Savola, Paula; Mustjoki, Satu; Schlenner, Susan M; Liston, Adrian; Dubois, Bénédicte; Goris, An
Abstract: The role of somatic variants in diseases beyond cancer is increasingly being recognized, with potential roles in autoinflammatory and autoimmune diseases. However, as mutation rates and allele fractions are lower, studies in these diseases are substantially less tolerant of false positives, and bio-informatics algorithms require high replication rates. We developed a pipeline combining two variant callers, MuTect2 and VarScan2, with technical filtering and prioritization. Our pipeline detects somatic variants with allele fractions as low as 0.5% and achieves a replication rate of >55%. Validation in an independent data set demonstrates excellent performance (sensitivity > 57%, specificity > 98%, replication rate > 80%). We applied this pipeline to the autoimmune disease multiple sclerosis (MS) as a proof-of-principle. We demonstrate that 60% of MS patients carry 2–10 exonic somatic variants in their peripheral blood T and B cells, with the vast majority (80%) occurring in T cells and variants persisting over time. Synonymous variants significantly co-occur with non-synonymous variants. Systematic characterization indicates somatic variants are enriched for being novel or very rare in public databases of germline variants and trend towards being more damaging and conserved, as reflected by higher phred-scaled combined annotation-dependent depletion (CADD) and genomic evolutionary rate profiling (GERP) scores. Our pipeline and proof-of-principle now warrant further investigation of common somatic genetic variation on top of inherited genetic variation in the context of autoimmune disease, where it may offer subtle survival advantages to immune cells and contribute to the capacity of these cells to participate in the autoimmune reaction.